2014
DOI: 10.1016/j.biomaterials.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Discrete microstructural cues for the attenuation of fibrosis following myocardial infarction

Abstract: Chronic fibrosis caused by acute myocardial infarction (MI) leads to increased morbidity and mortality due to cardiac dysfunction. We have developed a therapeutic materials strategy that aims to mitigate myocardial fibrosis by utilizing injectable polymeric microstructures to mechanically alter the microenvironment. Polymeric microstructures were fabricated using photolithographic techniques and studied in a three-dimensional culture model of the fibrotic environment and by direct injection into the infarct zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…The use of the MRS engineered with these specifications was based on previous data showing that the empty MRS can inhibit NIH 3T3 fibroblast proliferation and down regulate expression of myofibroblast markers (collagen I, VI and α-smooth muscle actin) when seeded in a 3D culture system [17]. These studies were recently extended by showing that intramyocardial delivery of the empty MRS alone is sufficient to limit fibrosis to an ischemia-reperfusion model in vivo [32]. Moreover, studies examining cardiac myocyte remodeling in 3D cultures showed that the presence of microrods influence cardiac myocyte size, protein content, myofibrillar alignment and gene expression, indicating that the physical cues of the microenvironment can play a significant role in regulating cellular function [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the MRS engineered with these specifications was based on previous data showing that the empty MRS can inhibit NIH 3T3 fibroblast proliferation and down regulate expression of myofibroblast markers (collagen I, VI and α-smooth muscle actin) when seeded in a 3D culture system [17]. These studies were recently extended by showing that intramyocardial delivery of the empty MRS alone is sufficient to limit fibrosis to an ischemia-reperfusion model in vivo [32]. Moreover, studies examining cardiac myocyte remodeling in 3D cultures showed that the presence of microrods influence cardiac myocyte size, protein content, myofibrillar alignment and gene expression, indicating that the physical cues of the microenvironment can play a significant role in regulating cellular function [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Although several biomaterials have been identified to reduce tissue stiffness or inhibit cardiac fibrosis, it remains to address whether they can be synergistically used in PSC‐based therapies. Microstructures of hyaluronic acid or hydrogel (fabricated by photolithography) were shown to anchor fibroblasts and mitigate cardiac fibrosis . MMPs (e.g., MMP2, MMP9, and MMP13) are required to correctly degrade the implanted scaffolds and endogenous natural ECM, allowing for stem cell migration and angiogenesis .…”
Section: Convergences Of Antifibrotic Strategies and Cell‐based Therapymentioning
confidence: 99%
“… 10 . For a detailed description of how cuboidal or rod-like PEG-microparticles were fabricated via photolithography, see refs 12 and 27 , respectively.…”
Section: Methodsmentioning
confidence: 99%